The Insights and Illusions of Consumption Measurements - Erich Battistin; Michele De Nadai; Nandini Krishnan (Institute of Labor Economics (IZA), 2020)
While household well-being derives from long-term average rates of consumption, welfare comparisons typically rely on shorter-duration survey measurements. We develop a new strategy to identify the distribution of these long-term rates by leveraging a large-scale randomization in Iraq that elicited repeated short-duration measurements from diaries and recall questions. Identification stems from diary-recall differences in reports from the same household, does not require reports to be error-free, and hinges on a research design with broad replicability. Our strategy delivers practical and costeffective suggestions for designing survey modules to yield the closest measurements of consumption well-being. In addition, we find little empirical support for the claim that acquisition diaries yield the most accurate measurement of poverty and inequality and offer new insights to interpret and reconcile diary-recall differences in household surveys.
Keywords: C81; D31; D63; E21; I32; 330; modes of data collection; measurement of inequality and poverty; household surveys